Pemberian Hadiah Pada Tabungan Sajadah Di Baitul Maal Wat Tamwil Nuansa Umat (BMT NU) Jawa Timur Cabang Larangan Perspektif Fatwa DSN-MUI No.86/DSN-MUI/XII/2012 - Hanafi Yunus; Lailiyatun Nuriyah (TERAJU: Jurnal Syariah dan Hukum, 2022)
This article examines the ujrah of Al-Qur’an readers at the public cemetery of Keude Blang village, East Aceh, from the perspective of muamalat fiqh. The author uses the muamalat fiqh theory. From the results of research in Keude Blang Village, East Aceh, it can be concluded that the ujrah for renting a Quran reader at the Public Cemetery has been practiced since time immemorial and for ujrah itself the tariff has been set at IDR 300,000 per day for one person and in Keude Blang it has also been formed a special group of readers of the Koran as many as 6 people in one group. In fiqh muamalat, it is permissible to rent an Al-Qur’an reader, but it is necessary to understand that reading the Koran is an act of worship and not having the intention of reading the Koran is a profession to earn money and instill a sense of sincerity in the heart without expecting anything in return. From humans but does this to worship and help fellow Muslims and considers the ujrah given to the readers of the Koran in public cemeteries as alms. The terminology of prizes in raising funds for Islamic Financial Institutions still requires a more detailed explanation. In some literature there are other terms that are similar to gifts, namely rewards, 'athaya, and bonuses. One of the sharia financial institutions is the Baitul Maal wa Tamwil (BMT) or also known as "Koperasi Syari'ah" which is a syari'ah financial institution that functions to raise funds and distribute funds to its members and usually operates on a micro scale. Here the author examines the BMT NU Prohibition Branch which has several sharia products, but the one that will be discussed by the author is the SAJADAH Savings (Wadiah Time Savings with Prizes). The tighter competition between Islamic banks made the DSN-MUI issue a fatwa which became the basis for the practice of giving gifts in the wadiah contract in Islamic banks as well as the DSN-MUI fatwa. So the DSN-MUI Fatwa No.86 / DSN-MUI / XII / 2012 was formed. The focus of this research is how the practice of giving gifts to SAJADAH savings at BMT NU Larangan Branch in Blumbungan Village, Larangan District, Pamekasan Regency and how the perspective of Fatwa DSN-MUI No. 86 of 2012 concerning the giving of prizes to SAJADAH Savings at BMT NU, Larangan. The purpose of this research is to know the practice of giving gifts to SAJADAH savings at BMT NU Larangan Branch in Blumbungan Village, Larangan District, Pamekasan Regency and to know the perspective of Fatwa DSN-MUI No. 86 of 2012 concerning giving gifts to SAJADAH savings at BMT-NU, Larangan Branch in Blumbungan Village, Larangan District, Pamekasan Regency. The research method used in this research is a type of normative-empirical research and a qualitative research approach that aims to make a systematic description of the picture, the facts, with interview techniques and direct observation and then draw the conclusions. The practice of giving prizes to SAJADAH savings products at BMT NU Larangan Branch in Blumbungan Village, Larangan District, Pamekasan Regency is the practice of giving gifts to savings customers with the contract used, namely the wadi'ah contract. In this practice, the customer gets a gift given by the BMT, which gift was not agreed upon at the beginning of the contract. The contract used in savings is appropriate. In the perspective of DSN-MUI Fatwa No. 86 of 2012, the practice of giving prizes to SAJADAH products at BMT NU Prohibition Branch is legal, because it was not agreed upon at the beginning of the contract.